2011
DOI: 10.5194/acp-11-8189-2011
|View full text |Cite
|
Sign up to set email alerts
|

Variability of aerosol optical properties in the Western Mediterranean Basin

Abstract: Abstract. Aerosol light scattering, absorption and particulate matter (PM) concentrations were measured at Montseny, a regional background site in the Western Mediterranean Basin (WMB) which is part of the European Supersite for Atmospheric Aerosol Research (EUSAAR). Off line analyses of 24 h PM filters collected with Hi-Vol instruments were performed for the determination of the main chemical components of PM. Mean scattering and hemispheric backscattering coefficients (@ 635 nm) were 26.6±23.2 Mm −1 and 4.3±… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

21
67
5

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 94 publications
(99 citation statements)
references
References 60 publications
21
67
5
Order By: Relevance
“…Values of the single scattering albedo measured in this study are comparable with values reported at several other sites in the Central and Western Mediterranean region for pollution aerosols (Mallet et al, 2003(Mallet et al, , 2013Meloni et al, 2006;Saha et al, 2008;Di Biagio et al, 2009;Pandolfi et al, 2011). The single scattering albedo from these studies varies in the range 0.84-0.95 at 440 nm, 0.76-0.98 at 500-550 nm, and 0.80-0.87 at 870 nm.…”
Section: Particle Size Distributionssupporting
confidence: 75%
See 1 more Smart Citation
“…Values of the single scattering albedo measured in this study are comparable with values reported at several other sites in the Central and Western Mediterranean region for pollution aerosols (Mallet et al, 2003(Mallet et al, , 2013Meloni et al, 2006;Saha et al, 2008;Di Biagio et al, 2009;Pandolfi et al, 2011). The single scattering albedo from these studies varies in the range 0.84-0.95 at 440 nm, 0.76-0.98 at 500-550 nm, and 0.80-0.87 at 870 nm.…”
Section: Particle Size Distributionssupporting
confidence: 75%
“…In spite of this, the characterization of the optical properties of anthropogenic aerosols in this part of the basin remains only limited to coastal and inland regions (Mallet et al, 2003(Mallet et al, , 2011(Mallet et al, , 2013Lyamani et al, 2006;Estelles et al, 2007;Saha et al, 2008;Esteve et al, 2012;Piazzola et al, 2012;Pandolfi et al, 2011Pandolfi et al, , 2014, or remote islands actually far from the strong influence of continental outflows (Lyamani et al, 2015). Moreover, the majority of these studies uses remote-sensing measurements and analyse aerosol properties integrated over the entire atmospheric column, without information on their vertical variability.…”
mentioning
confidence: 99%
“…The MAAP instrument uses a constant value of 6.6 m 2 g −1 , which is recommended by the manufacturer. However, this value has been the subject of strong debate (Pan et al, 2011;Pandolfi et al, 2011;Healy et al, 2012;Crippa et al, 2013). Here, the aerosol light absorption measured using the MAAP in the JQ tunnel was compared with EC determined from the collected filters by means of a Sunset analyser.…”
Section: Mass Absorption Coefficientmentioning
confidence: 99%
“…[8] collected measurements of dry (RH < 40%) aerosol P M10 mass concentrations (gravimetric masses from 24h filters) and optical properties (scattering coefficients with Nephelometer AURORA 3000, Ecotech), in the period 2010-2014, at the Montseny regional background station (middle altitude emplacement within the Montseny Natural Park, Spain: 41…”
Section: Observationsmentioning
confidence: 99%